2018
DOI: 10.1080/13854046.2018.1472297
|View full text |Cite
|
Sign up to set email alerts
|

National Association of Psychometrists: 2015 professional practices and salary survey of U.S. and Canadian psychometrists

Abstract: The current survey may be used as a baseline for further study of the income and practices of psychometrists in the United States and Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Billing for neuropsychological assessments provides a good example of an opportunity to improve cost-efficiency through adoption of computer-assisted assessments. On national salary surveys, the median reported time spent on a neuropsychological evaluation was 6 hr (Sweet et al, 2015) and most psychometrists reported they spent 1–2 hr scoring per evaluation (Kippie et al, 2019). Based on these numbers, even a conservative estimate of a 30-min reduction in scoring time through the use of computer-assisted assessments could have saved Medicare over 11 million dollars during 2019 alone (Centers for Medicare & Medicaid Services, 2020).…”
Section: Implications Of Computer-assisted Assessments For Patients A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Billing for neuropsychological assessments provides a good example of an opportunity to improve cost-efficiency through adoption of computer-assisted assessments. On national salary surveys, the median reported time spent on a neuropsychological evaluation was 6 hr (Sweet et al, 2015) and most psychometrists reported they spent 1–2 hr scoring per evaluation (Kippie et al, 2019). Based on these numbers, even a conservative estimate of a 30-min reduction in scoring time through the use of computer-assisted assessments could have saved Medicare over 11 million dollars during 2019 alone (Centers for Medicare & Medicaid Services, 2020).…”
Section: Implications Of Computer-assisted Assessments For Patients A...mentioning
confidence: 99%
“…Together these units represent the maximum number of unique assessments billed for in 2019. Based on reports of neuropsychologist and technician time use (Kippie et al, 2019; Sweet et al, 2015), the majority of assessments take more than 30 min to administer and score and thus require additional units of 96137 or 96139, the codes for each additional 30-min unit of testing or scoring by a provider or technician, respectively. Using a conservative estimate that 20% of assessments only require one 30-min billing code, the number of assessments with additional 30-min codes would be 141,560 (176,950 × .80) for providers and 129,797.6 (162,247 × .80) for technicians.…”
mentioning
confidence: 99%